SISTEM PERSAMAAN LINEAR ATAS RING KOMUTATIF - SRRM, Titi udjiani (MATEMATIKA, 2006)
Linear systemsÂ equations over commutatif ring are linear systemsÂ equations with the coeffici-ents of these equations are elements from commutatif ring. This paper discusses about basic theorems on solution of linear systems equations over commutatif ring. The basic theorems will be found by using characteristic of ideal ,annihilator and rank of coefficient matrices of linear systems equations over commutatif ring. The idealÂ is generated by minors of coefficient matrices of linear systems equations over commutatif ring. Computing the annihilator of ideal we get the rank of coefficient matrices of linear systems equations over commutatif ring